BVDV comprehensive studies and species identification in high-yielding livestock populations in the Sverdlovsk Oblast - N. A. Bezborodova; V. V. Kozhukhovskaya; E. V. Pechura; N. A. Martynov; O G. Tomskikh; A. N. Vasilyeva (Ветеринария сегодня)
The paper presents results of comprehensive studies of the bovine viral diarrhea virus circulating in cattle populations in the Sverdlovsk Oblast. In 2018–2024, 113 biological samples were tested using polymerase chain reaction, the viral RNA specific regions were detected in 15.9% of cases.The BVDV RNA was isolated from biological samples collected from aborted cows (61.1%) and calves under one month of age (38.9%). Based on typing results, the virus isolates detected in four samples (nasopharyngeal swabs of calves, suspension prepared from aborted fetus organs and placenta) were classified as BVDV-1 virulent genotypes. The BVDV RNA, Mycoplasma bovis and Chlamydophila pecorum DNAs were detected simultaneously in 44% of vaginal swab samples from aborted cows and, in single cases, in the placenta and parenchymatous organs of dead calves; BVDV RNA and Bovine herpesvirus type 1 DNA were detected in 16% of pathological samples from dead calves. In some cases, the BVDV RNA, Chlamydophila pecorum and Mycoplasma bovigenitalium DNA were detected in nasopharyngeal swabs of calves. The “Comprehensive Programme for Biosecurity and Bovine Viral Diarrhea Situation Improvement in Agricultural Organizations”implemented in the Sverdlovsk Oblast in 2018 resulted in decreased number of agricultural establishments affected by bovine viral diarrhea. Acute and persistent infection forms among young animals were recorded 4 and 3.5 times less frequently, respectively, but at the same time, a 2.5-fold increase in the diagnosed latent form of the disease was observed in adult livestock, which is associated with an increase in the number of laboratory tests performed.